Genotoxic stress modulates the release of exosomes from multiple myeloma cells capable of activating NK cell cytokine production: Role of HSP70/TLR2/NF-kB axis. (4th March 2017) - Vulpis, Elisabetta; Cecere, Francesca; Molfetta, Rosa; Soriani, Alessandra; Fionda, Cinzia; Peruzzi, Giovanna; Caracciolo, Giulio; Palchetti, Sara; Masuelli, Laura; Simonelli, Lucilla; D'Oro, Ugo; Abruzzese, Maria Pia; et al.
ABSTRACT: Exosomes are a class of nanovesicles formed and released through the late endosomal compartment and represent an important mode of intercellular communication. The ability of anticancer chemotherapy to enhance the immunogenic potential of malignant cells mainly relies on the establishment of the immunogenic cell death (ICD) and the release of damage-associated molecular patterns (DAMPs). Here, we investigated whether genotoxic stress could promote the release of exosomes from multiple myeloma (MM) cells and studied the immunomodulatory properties they exert on NK cells, a major component of the antitumor immune response playing a key role in the immunosurveillance of MM. Our findings show that melphalan, a genotoxic agent used in MM therapy, significantly induces an increased exosome release from MM cells. MM cell-derived exosomes are capable of stimulating IFNγ production, but not the cytotoxic activity of NK cells through a mechanism based on the activation of NF-κB pathway in a TLR2/HSP70-dependent manner. Interestingly, HSP70 + exosomes are primarily found in the bone marrow (BM) of MM patients suggesting that they might have a crucial immunomodulatory action in the tumor microenvironment. We also provide evidence that the CD56 high NK cell subset is more responsive to exosome-induced IFNγ production mediated by TLR2 engagement. All together, these findings suggest a novel mechanism of synergism between chemotherapy and antitumor innate immune responses based on the drug-promotion of nanovesicles exposing DAMPs for innate receptors.